The effect of constant darkness and circadian resynchronization on the recovery of alcohol hangover - Karadayian, Analia Graciela (2014)
Alcohol hangover (AH) is a particular state after binge-like drinking. AH begins when ethanol is absent in plasma and is characterized by a cluster of physical and psychological symptoms. Alcohol disrupts circadian patterns of behavioral and physiological parameters; however, the involvement of circadian clock on the recovery of AH was not explored. Our aim was to study the effect of continuous darkness and the possible involvement of the circadian clock in the recovery time of neuromuscular impairment and anxiety related-behavior due to AH. Male Swiss mice were habituated to 12:12 L:D or continuous darkness. Each group was injected i.p. either with saline (control group) or with ethanol (3.8 g/kg BW) (hangover group). Motor performance and anxiety phenotype were evaluated at a basal point (ZT0) and every 2 h up to 20 h after blood alcohol levels were close to zero (hangover onset). A third group was subjected to a phase advance during which a hangover episode was induced and behavioral tests were carried out for each group of treatment and resynchronization day. Constant darkness resulted to be in a faster recovery of both motor and anxiety impairments in AH compared with the recovery pattern observed under normal light–dark conditions. Mice suffering from a phase shift exhibited behavioral disruptions due to both AH and phase advance. Results indicated that a synchronized circadian clock is necessary for an adequate recovery of alcohol hangover symptoms.